Silicone gel breast implants : past, present, and future = Silikonski implantati za dojke : prošlost, sadašnjost i budućnost - Pirjavec, Aleksandra (Array, 2020)
The authors have provided an in-depth review of the history of saline and silicone gel–filled breast implants. In the history of medicine, no devices have been more scrutinized and thoroughly studied than breast implants. Although we as plastic surgeons recognize and appreciate the benefits that our patients derive from these devices, society as a whole continues to remain skeptical. The reasons for this are complex and multifactorial but appear to be fueled by the media, oppositional organizations, and several trial lawyers. Prior to 1990, when the silicone gel implant controversy began, there were only eight indexed publications that dealt with the issue of silicone gel breast implants. Since 1990, there have been more than 500 indexed publications dealing with silicone gel implants. At the time of the moratorium in 1992, we as plastic surgeons did not have a leg to stand on because there was a paucity of scientific evidence to support our observations that silicone breast implants were safe and effective devices.